ORGANISATIONAL CULTURE AND JOB SATISFACTION: A STUDY OF FACULTY IN HIGHER EDUCATION - Mahindru, Dr. Rinku; Kapoor, Dr. Nidhi (The journal of contemporary issues in business and government, 2022)
The succession of attitudes and behaviors espoused by employees of a given organization that affect its function and overall well-being is referred to as organisational culture. It is vital for any organization's success and plays a critical part in shaping an organization's strategies. Employee opinions and attitudes toward the working environment and work experience are measured by job satisfaction. The purpose of the present study was to explore the faculty of the University of Delhi's attitude towards organisational culture, their job satisfaction levels, and the relationship between the components of culture and job satisfaction levels. Data in this study were collected from a total number of 100 faculty members of University of Delhi. It further examines demographics (gender, age, experience in present college and type of college) on job satisfaction levels and culture components. Data analysis indicated a moderate level of job satisfaction among the faculty of University of Delhi, which needs to be improved. There was a significant positive correlation between job satisfaction levels and the organisational culture components; therefore, improvement in culture is expected to lead to better job satisfaction levels.